Impact of Topical Pure Honey Application on Radiation-induced Oral Mucositis in Patients Receiving Radiation Therapy - Raina Jose; Rincy T. Issac (International Journal of Oncological Nursing and Practices, 2024)
This quasi-experimental study assessed the effects of pure honey on radiation-induced oral mucositis in patients with head and neck cancer undergoing radiation therapy in Kottayam. The primary objectives were to evaluate the severity of oral mucositis in both experimental and control groups, determine the effectiveness of honey in alleviating symptoms, and examine the relationship between mucositis severity and selected demographic variables. Utilizing Bertalanffy’s General System Model as a conceptual framework, a quantitative approach was employed. The study included 60 patients, divided into two groups of 30, selected through purposive sampling. The severity of oral mucositis was measured using a standardized Oral Mucositis Assessment Scale on the first day. In the experimental group, pure honey was applied at three intervals: 15 minutes before, 15 minutes after, and 6 hours after radiation therapy over five days. The control group received no intervention. A post-test assessment using the same scale was conducted on the fifth day. Results indicated that the experimental group exhibited a significant reduction in the severity of mucositis post-intervention, suggesting that honey application effectively alleviates symptoms associated with radiation therapy. Furthermore, no significant correlations were found between pre-test severity scores and the demographic variables examined. In conclusion, the study supports the use of topical pure honey as a beneficial treatment for reducing radiation-induced oral mucositis in head and neck cancer patients receiving radiation therapy, highlighting its potential as a simple and effective intervention in clinical practice.
Keywords: Effect; head and neck cancer patients; radiation induced oral mucositis; radiation therapy; topical application of pure honey